Intergenerational Sharing of Unhedgeable Inflation Risk - Damiaan H.J. Chen; Roel M.W.J. Beetsma; Sweder J.G. van Wijnbergen (Tinbergen Institute, 2022)
We explore how members of a collective pension scheme can share inflation risks in the absence of suitable financial market instruments. Using intergenerational risk sharing arrangements, risks can be allocated better across the various participants of a collective pension scheme than would be the case in a strictly individual- or cohort-based pension scheme, as these can only lay off risks via existing financial market instruments. Hence, intergenerational sharing of these risks enhances welfare. In view of the sizes of their funded pension sectors, this would be particularly beneficial for the Netherlands and the U.K
Keywords: C61; E21; G11; G23; 330; pension funds; intergenerational risk sharing; unhedgeable inflation risk; incomplete markets; welfare loss